Genetic gains from cycles of fullsib recurrent selection for low nitrogen tolerance in a tropical maize population - Omoigui, L.; Alabi, S.; Ado, S.; Ajala, S.; Kamara, A. (2006)
Nitrogen stress is a major nutrient constraint to maize productivity in the Northern Guinea savanna of West and Central Africa. Thus, improved maize germplasm tolerant to low N with the capacity to utilize N more efficiently together with improved agronomic practices appear to be the primary control measure for low input management. As part of the breeding strategy, effort is currently being made to use full-sib family selection to improve maize populations for low N tolerance. This study assessed the genetic gain after three cycles of full-sib recurrent selection which were applied on a low N pool-yellow endosperm type maize population derived from the intermating of a germplasm collection from CIMMYT, in order to improve tolerance to low soil nitrogen. Three cycles of full-sib recurrent selection for low N tolerance resulted in genetic gains of 2.3 and 1.9 cycleE-1 grain yield at low and high N, respectively. Selection also increased stay green ability and kernel weight with a corresponding gain of 17.7 and 4.7 cycleE-1, respectively. The observed gain compared favourably well with the expected genetic gain for days to 50 silk, anthesis-silking interval, plant aspect and stay green. Although absolute gains were small for grain yield and other secondary traits, the magnitude of change in the mean of grain yield and other agronomic traits after three cycles of selection suggests that changes in gene frequencies had occurred. This clearly points to the usefulness of full-sib recurrent selection as a population improvement procedure for improved performance to low soil nitrogen tolerance.